THE CHARACTERIZATION OF AMANDA COLLIER IN NICHOLAS SPARKS’ THE BEST OF ME (2011) - Dewi, Ni Komang Karisma; Suwastini, Ni Komang Arie; Jayantini, I Gusti Agung Sri Rwa (Universitas Pendidikan Ganesha, 2021)
People can learn human characterization by reading a novel since all characters reflect real-life human characteristics. The study aimed to describe the characterization of Amanda Collier as the female main character in Nicholas Sparks’ The Best of Me (2011). By employing qualitative data analysis from Miles, Huberman, and Saldaña, the present study incorporated the data collection, data condensation, data display and conclusion drawing into a simultaneous, interactive process that was conducted repeatedly to build the research’s trustworthiness. It was revealed that as the main character, Amanda Collier was mainly described as a pretty school girl that made her popular at her school. When she grew up, was also described as a beautiful woman. Amanda Collier was rich and had a college education. Amanda Collier had strong curiosity and she was brave and impulsive. Furthermore, she was also described as generous because she made time to volunteer in a hospital to take care of children with cancer. From this study, it is implied that while enjoying the romance, readers of Nicholas Sparks’ The Best of Me can also learn various good characters reflected in Amanda Collier’s characterizations.